2018
DOI: 10.3390/life8040047
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Aminonitriles with Aminothiols: A Way to Thiol-Containing Peptides and Nitrogen Heterocycles in the Primitive Earth Ocean

Abstract: The Strecker reaction of aldehydes with ammonia and hydrogen cyanide first leads to α-aminonitriles, which are then hydrolyzed to α-amino acids. However, before reacting with water, these aminonitriles can be trapped by aminothiols, such as cysteine or homocysteine, to give 5- or 6-membered ring heterocycles, which in turn are hydrolyzed to dipeptides. We propose that this two-step process enabled the formation of thiol-containing dipeptides in the primitive ocean. These small peptides are able to promote the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The Pinner reaction of nitriles with thiols under aqueous conditions leads to thioesters . We have shown that using this reaction, aminonitriles can be transformed into aminothioesters under prebiotic conditions . Such chemistry could bridge a prebiotic chemistry dominated by nitriles and the Strecker reaction, and the thioester world imagined by de Duve .…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The Pinner reaction of nitriles with thiols under aqueous conditions leads to thioesters . We have shown that using this reaction, aminonitriles can be transformed into aminothioesters under prebiotic conditions . Such chemistry could bridge a prebiotic chemistry dominated by nitriles and the Strecker reaction, and the thioester world imagined by de Duve .…”
Section: Introductionmentioning
confidence: 93%
“…MALDI mass analysis of this precipitate demonstrated that it was constituted of a complex mixture containing some relatively high mass molecules (up to at least 1500). However, the structure of these products, which in principle could be polythiazolines (from the reactions of nitriles with aminothiols) or polypeptides, (Cys) n (from thiazoline rings hydrolysis), was not clearly identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we have reported the synthesis of various dipeptides starting from cysteine and aminonitriles under plausible prebiotic conditions [11]. Such dipeptides, as well as longer peptides containing thiol groups, could have been promoters of other reactions in the “thioester world” proposed by De Duve [12,13], perhaps in a way similar to what is happening today in the non-ribosomal synthesis of peptides [14].…”
Section: Introductionmentioning
confidence: 98%